Avaliação da sustentabilidade em agroecossistemas de base convencional, orgânica e agroecológica com a aplicação do método MESMIS - Feitosa, Alcebiades Gomes Bezerra (2023)
In a world that is constantly evolving, the search for sustainable solutions in agriculture has become a pressing need. Sustainable rural development and the promotion of sustainability in agroecosystems are at the heart of this challenge. This study evaluates and compares sustainability indexes obtained by different rural enterprises using MESMIS - Framework for Evaluation of Natural Resource Management Systems Incorporating Sustainability Indicators. The method led to the application of a survey with 36 questions, comprising the Environmental, Social and Economic dimensions, that comprised the evaluation of 29 different properties located in three districts of the Metropolitan Region of Natal, state of Rio Grande do Norte. Regarding the dimension evaluated in the study, we can highlight that, overall, 65% have a size of up to 5 hectares, 25% between 5 and 10 hectares, and only 10% over 10 hectares. Among these, 66% use conventional farming techniques, 20% organic and 14% agroecological. All the properties evaluated have agriculture as their main income-generating activity. From the analysis of the sustainability indexes generated by MESMIS, it was possible to observe that the highest index achieved was 4.16, obtained by an agroecological crop, while the lowest index was 2.67, by a conventional crop. The average sustainability index, stratified by form of production, was 3.01 for conventional production, 3.70 for organic production and 4.04 for agroecological production. Some positive highlights among the environmental, social and economic sustainability indexes found in agroecological-based crops are, respectively: fertilization and pest control; effluent treatment and food security; use of innovations and production diversification. The same highlights in organic-based crops were: fertilization and pest control; agricultural training and access to public policies; access to credit and relative productivity. Finally, the positive highlights in conventional crops were: crop rotation; housing infrastructure and family succession; financial satisfaction. The comparative analyzes carried out showed that the arithmetic method for calculating indexes, despite reflecting a large part of the reality of agroecosystems, required qualitative analyzes to better understand them. Several advantages were found for farmers who opt for a more sustainable farming, such as greater productivity per area, profitability, improved soil quality and food security.